The Effect Of Pricing Strategy and Business Capital on UMKM Income In Sidorejo Hilir Medan - Laras Fitri Aini Hasibuan; Bio Hasian Siregar; Hera Wati (Outline Journal of Management and Accounting, 2025)
Micro, Small, and Medium Enterprises (MSMEs) play a strategic role in the Indonesian economy, but still face various challenges that affect their income. This study aims to analyze the influence of pricing strategies and business capital on the income of MSMEs in Sidorejo Hilir, Medan. The research method used is a quantitative approach with data collection techniques through questionnaires given to 30 MSMEs as research samples. The data obtained were analyzed using multiple regression tests with the help of SPSS 23.0 software. The results of the study indicate that pricing strategies do not significantly affect MSME income, while business capital has a positive and significant effect on income. Simultaneously, pricing strategies and business capital have a significant influence on MSME income, with a contribution of 54.6%, while 45.4% is influenced by other factors not examined in this study. The results of this study provide insights for MSME actors to focus more on business strategies on business capital management to increase their income.